The SCAMPER method as an effective tool for designing innovative organizational solutions - Kafel, Tomasz (Metody i techniki zarządzania. Inspiracje dla teorii i praktyki, 2020)
A detailed description of the assumptions and stages of the procedure of the relatively poorly recognized in Poland SCAMPER method is presented. An analysis of examples of its use in solving organizational problems was carried out. The first part of the study points to the growing importance of lateral (divergent) thinking in the face of the challenges faced by contemporary organizations. The next part lists the determinants of the effective use of inventive methods in creating organizational innovations. The next part of the study is a broad description of the SCAMPER method, and above all: discussion of questions determining the direction of transformation of the examined object, and the proposed stages of the procedure. The final part describes examples of the use of the SCAMPER method in creating organizational innovations, including in the area of designing the Canvas business model.